Poster: A Fresh Look at Optical Interferometry - Kissinger, Thomas (Cranfield University, 2016)
Poster presented by Thomas Kissinger at Set for Britain 2016 event in the UK parliament on 07.03.2016. Abstract: Optical interferometry is a widely used technique for ultra-precision distance measurements in many areas of science and technology, enabling fundamental physical experiments, such as the hunt for gravitational waves, and underpinning important industrial technologies, such as semiconductor fabrication. My particular research deals with the question on how multiple measurements at different points can be taken simultaneously using only one instrument. This can be achieved by appropriately modulating the optical wavelength of the laser used and a very simple way to perform these measurements is the signal processing technique developed during my PhD thesis project. A key advantage of this approach is that it reduces the number of optical components needed and instead shifts complexity of the measurements into the electronics, potentially enabling very cost-effective measurements. As this technology is very new many potential applications still remain unexplored.
Keywords: Interferometry'; 'Optics'; 'Photonics'; 'Measurement science'; 'Optical Physics not elsewhere classified'; 'Photonics; Optoelectronics and Optical Communications'; 'Photodetectors; Optical Sensors and Solar Cells'; 'Photonics and Electro-Optical Engineering (excl. Communications)'